High prevalence of Chlamydia trachomatis infection among women attending STD and gynecology clinics in Jiangsu province, China: A cross-sectional survey. Issue 46 (19th November 2021) - Hu, Haiyang; Zhou, Ying; Shi, Lingen; Lu, Jing; Zhang, Zhi; Xu, Xiaoqin; Huan, Xiping; Fu, Gengfeng
Abstract : Abstract: Epidemics of Chlamydia trachomatis (CT) infection among women are major global public health concerns. This study examined the prevalence of CT infection and associated factors among women attending sexually transmitted disease (STD) and gynecology clinics in Jiangsu province, China. A cross-sectional survey was conducted among women attending STD and gynecology clinics in the province during 2018 to 2019. Socio-demographic and behavioral information were collected through face-to-face questionnaire survey. Cervical swab specimens were collected to test for CT. Chi square tests were used to compare differences in CT prevalence between subgroups of characteristics. Multivariate logistic regression analysis was used to identify factors associated with CT infection. A total of 2664 participants were enrolled. The prevalence of CT infection was 16.6% (95% confidence interval: 15.0%–18.1%). Of those, CT prevalence among participants from STD clinics (19.4%) and South Jiangsu (18.5%) were higher. Female outpatients who were service personnel (adjusted odds ratio [aOR] = 1.667, P = .004) or farmers (aOR = 1.593, P = .039), lived in South Jiangsu (aOR = 1.796, P = .004), and were from STD clinics (aOR = 1.608, P = .022) were more likely to infect CT. Our study showed a high prevalence of CT infection among women attending STD and gynecology clinics in Jiangsu province, China. CT screening, surveillance and treatment promotion should therefore be of top priority on the CT prevention agenda.